Insider threat: A critical review of the literature - Munshi, Asmaa; Issa, Tomayess (IADIS Press, 2012)
Threat from internal sources is one of the most serious problems organizations word-wide encounter nowadays as it is difficult to overcome. Currently, all organizations and sectors are facing the insider threats' problems to computer assets. This paper presents a descriptive literature review about insider threat and some classification, for example: insiders and insider threat definitions, and the classification of the insider attack. Moreover, the paper aims to examine the current and previous academic literature to identify the risks associated with insider threats, and finally, it describes some of the previous insider threat models and some of the future research ideas.